Three ecologies, transversality and victimization: the case of the British Petroleum oil spill - Spencer, Dale C. (Crime, law and social change, 2013)
A number of critiques of the burgeoning field of green criminology have recently been articulated in the literature. The aim of this article is to begin to demonstrate what green criminological work responsive to these critiques might look like. The two primary critiques we are concerned with here are (1) that there has been little intellectual sharing between the fields of green criminology and victimology, and (2) that green criminological work has failed to be reflexive about the modernist assumptions it has largely adhered to. In response to these critiques, we draw on the theorizing of poststructuralist Felix Guattari to analyze the various interrelated layers of victimization in the 2010 British Petroleum oil spill case in the Gulf of Mexico.